The presence of C. S. Peirce’s semiotics in Gilles Deleuze’s reflections on signs - da Costa Santos, Rogério (2020)
This paper investigates the presence of C. S. Peirce’s semiotics in Gilles Deleuze’s philosophy. The interest in Peirce’s ideas came from the partnership that Deleuze established with Felix Guattari, and is manifest in the use of the concepts of semiotics and diagram in his joint work “A Thousand Plateaus.” Later, Deleuze would make deeper use of Peirce’s semiotics in his books and courses on Film.